An endoplasmic reticulum-targeting and ratiometric fluorescent probe for hypochlorous acid in living cells based on a 1, 8-naphthalimide derivative. (21st October 2020) - Ma, Qiujuan; Wang, Chunyan; Mao, Guojiang; Tian, Meiju; Sun, Jingguo; Feng, Suxiang
Abstract : A novel reticulum-targeting and ratiometric fluorescent probe for determining hypochlorous acid has been developed. Abstract : As a key reactive oxygen species (ROS), hypochlorous acid (HClO) plays a vital role in living systems. Ratiometric and endoplasmic reticulum-targeting probes for highly sensitive detection of hypochlorous acid are in demand. In this paper, we constructed a novel reticulum-targeting and ratiometric fluorescent probe for determining hypochlorous acid. The probe applied 4-aminonaphthalimide as the fluorescent group, employed the (2-aminoethyl)thiourea group as a specific recognition unit, and used the p -toluenesulfonamide group as the localization group of the endoplasmic reticulum. When HClO is absent, the probe underwent an intramolecular charge transfer (ICT) process and displayed green emission. In the presence of HClO, the ICT process was inhibited, which induced a 49 nm blue-shift of fluorescence emission from 533 nm to 484 nm. The ratiometric fluorescent probe exhibited high sensitivity and selectivity for HClO. Furthermore, the ratiometric fluorescent probe could work in a wide pH range. The fluorescence intensity ratios ( I 484nm / I 533nm ) exhibited a linear response to the concentration of HClO from 5.0 × 10 −7 to 1.0 × 10 −5 mol L −1 . The detection limit was evaluated to be 1.0 × 10 −7 mol L −1 for HClO. In addition, the probe displayed an excellent endoplasmic reticulum-targeting ability, and has been successfully applied for the confocal imaging of HClO in the endoplasmic reticulum of PC-12 cells with almost no cell toxicity. All of such outstanding properties demonstrated that it could be employed to sense HClO in the endoplasmic reticulum of living cells.